2018
DOI: 10.1007/s10461-018-2275-2
|View full text |Cite
|
Sign up to set email alerts
|

Couple Interdependence Impacts Alcohol Use and Adherence to Antiretroviral Therapy in Malawi

Abstract: In sub-Saharan Africa, harmful alcohol use among male drinkers is high and has deleterious consequences on adherence to antiretroviral therapy (ART), HIV clinical outcomes, and couple relationship dynamics. We conducted in-depth qualitative interviews with 25 Malawian couples on ART to understand how relationships influence adherence to ART, in which alcohol use emerged as a major theme. Almost half of men (40%) reported current or past alcohol use. Although alcohol use was linked to men's non-adherence, women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…Participants reported that male alcohol consumption, phone calls and community gossip triggered female RJ [100,103], and that women confronting their partners about infidelity led to arguments about whether the infidelity had occurred [92,99], which in turn escalated to physical and psychological IPV [80,87,88,92,95,100,102,103].…”
Section: Identified Mechanisms and Pathways From Infidelity And Rj Tomentioning
confidence: 99%
See 3 more Smart Citations
“…Participants reported that male alcohol consumption, phone calls and community gossip triggered female RJ [100,103], and that women confronting their partners about infidelity led to arguments about whether the infidelity had occurred [92,99], which in turn escalated to physical and psychological IPV [80,87,88,92,95,100,102,103].…”
Section: Identified Mechanisms and Pathways From Infidelity And Rj Tomentioning
confidence: 99%
“…Reports of bidirectional IPV (male-to-female and female-to-male) triggered by infidelity or RJ also emerged [87,89,90,95,100,102]. These confrontations usually included alcohol consumption, and increasingly severe physical IPV against women [87,89,102], sometimes resulting in femicide [90].…”
Section: Identified Mechanisms and Pathways From Infidelity And Rj Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also explored relationship quality among African couples in the context of HIV prevention (Belus, Kline, Carney, Myers, & Wechsberg, 2018), uptake and experience of HIV testing and counselling (Conroy, 2014, 2015; Darbes et al., 2014; Maman, Mbwambo, Hogan, Kilonzo, & Sweat, 2001; Tabana et al., 2013), and adherence to HIV treatment (Conroy, McKenna, & Ruark, 2019; Conroy et al., 2017). A qualitative study with young South African couples found that relationships characterised by mistrust, poor communication, and violence placed them at greater risk of HIV infection (Parker, Pettifor, Maman, Sibeko, & MacPhail, 2014), and young South African men who reported having positive dating relationships were more likely to report condom use (Gevers, Jewkes, & Mathews, 2013).…”
Section: Introductionmentioning
confidence: 99%